Origin of Excellent Charge Storage Properties of Defective Tin Disulphide in Magnesium/Lithium-Ion Hybrid Batteries - Xin Fan; Mike Tebyetekerwa; Yilan Wu; Rohit Ranganathan Gaddam; Xiu Song Zhao (Nano-Micro Letters, 2022)
Abstract Lithium-ion batteries (LIBs) are excellent electrochemical energy sources, albeit with existing challenges, including high costs and safety concerns. Magnesium-ion batteries (MIBs) are one of the potential alternatives. However, the performance of MIBs is poor due to their sluggish solid-state Mg2+ diffusion kinetics and severe electrode polarizability. Rechargeable magnesium-ion/lithium-ion (Mg2+/Li+) hybrid batteries (MLHBs) with Mg2+ and Li+ as the charge carriers create a synergy between LIBs and MIBs with significantly improved charge transport kinetics and reliable safety features. However, MLHBs are yet to reach a reasonable electrochemical performance as expected. This work reports a composite electrode material with highly defective two-dimensional (2D) tin sulphide nanosheets (SnS x ) encapsulated in three-dimensional (3D) holey graphene foams (HGF) (SnS x /HGF), which exhibits a specific capacity as high as 600 mAh g−1 at 50 mA g−1 and a compelling specific energy density of ~ 330 Wh kg−1. The excellent electrochemical performance surpasses previously reported hybrid battery systems based on intercalation-type cathode materials under comparable conditions. The role played by the defects in the SnS x /HGF composite is studied to understand the origin of the observed excellent electrochemical performance. It is found that it is closely related to the defect structure in SnS x, which offers percolation pathways for efficient ion transport and increased internal surface area assessable to the charge carriers. The defective sites also absorb structural stress caused by Mg2+ and Li+ insertion. This work is an important step towards realizing high-capacity cathode materials with fast charge transport kinetics for hybrid batteries.